CONTRACT AS AN ALGORITHM: INTRODUCTORY CONSIDERATIONS - Cvetković, Predrag (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Legal norms contained in the contract (also in the statutes, bylaws) and written in natural language can be subject of algorithmic conversion in certain phases of the contract circle (implementation, monitoring, control, interpretation). Application of the blockchain concept as a structural pattern opens the possibility of creating a contract with automated fulfillment: execution: a "smart" contract. Algorithmization is understood as a process that allows the text of the contract to be translated into a format that is understandable to software developers. To this end, the use of the following methodologies is proposed: design of pseudocode, application of formal logic`s symbols and flowchart. Successful conversion of legal prose into code requires cooperation between lawyers and programmers. The framework of that cooperation is the establishment of the so-called  "Legal Expert System"-LES): LES is a program conceived by lawyers  allows the algorithm to solve the problem of contract execution. Contract algorithmization should convert contracts from prose to code, while preserving its validity and efficiency. The sate of the art of the smart contracts’ contract developoment does not allow those contracts to regulate commercially complex scenarios: therefore, de lege lata, the application of smart contracts as a complete replacement for traditional (analogous) contracts is excluded. A potential objects of algorithmization are the primary instructions aimed at executing the characteristic performance of the contract. Contract algorithmization is an ongoing process and is here to stay. The significance of this process is indisputable: its scope, dynamics and assumptions are still only partially defined and tested. The necessary condition (but not a sufficient one is the view of the contract as an algorithm to be legitimized in the process of defining the contractual provisions. Further development will depend on the functioning of other elements in the environment in which coded contracts would function, and perhaps most of all on the commercial response to the whole process: to create contract as an algorithm must become a commercially viable behavior to be widely applied.
Keywords: contract; algorithm; smart contracts; pseudocode; formal logic